Intercalating Ultrathin MoO3 Nanobelts into MXene Film with Ultrahigh Volumetric Capacitance and Excellent Deformation for High-Energy-Density Devices - Wang, Yuanming; Wang, Xue; Li, Xiaolong; Liu, Rong; Bai, Yang; Xiao, Huanhao; Liu, Yang; Yuan, Guohui (Nano-Micro Letters, 2020)
The restacking hindrance of MXene films restricts their development for high volumetric energy density of flexible supercapacitors toward applications in miniature, portable, wearable or implantable electronic devices. A valid solution is construction of rational heterojunction to achieve a synergistic property enhancement. The introduction of spacers such as graphene, CNTs, cellulose and the like demonstrates limited enhancement in rate capability. The combination of currently reported pseudocapacitive materials and MXene tends to express the potential capacitance of pseudocapacitive materials rather than MXene, leading to low volumetric capacitance. Therefore, it is necessary to exploit more ideal candidate materials to couple with MXene for fully expressing both potentials. Herein, for the first time, high electrochemically active materials of ultrathin MoO3 nanobelts are intercalated into MXene films. In the composites, MoO3 nanobelts not only act as pillaring components to prevent restacking of MXene nanosheets for fully expressing the MXene pseudocapacitance in acidic environment but also provide considerable pseudocapacitive contribution. As a result, the optimal M/MoO3 electrode not only achieves a breakthrough in volumetric capacitance (1817 F cm−3 and 545 F g−1), but also maintains good rate capability and excellent flexibility. Moreover, the corresponding symmetric supercapacitor likewise shows a remarkable energy density of 44.6 Wh L−1 (13.4 Wh kg−1), rendering the flexible electrode a promising candidate for application in high-energy-density energy storage devices. Highlights: 1 All-pseudocapacitive and highly deformable MXene hybrid film is successfully fabricated by a facile and efficient vacuum-assisted filtration of ultrathin MoO3 nanobelts and delaminated MXene nanosheets. 2 The optimal M/MoO3 hybrid electrode delivers an ultrahigh volumetric capacitance of 1817 F cm−3 (545 F g−1), which exceeds large majority of previously reported MXene-based flexible electrodes. 3 The symmetric supercapacitor presents excellent energy density of 44.6 Wh L−1 (13.4 Wh kg−1), indicating the electrode promising in achieving high-energy-density devices.